Site-directed mutagenesis of helical lid of J15 lipase - Ho, Chern Min (2015)
Lid of lipases modulate the specificity of the substrate to the catalytic active site of lipase by interfacial activation. To address the role of lid on the substrate specificity, site-directed mutagenesis was used to modify the hydrophobicity of the lid by computer simulation and experimental approach. The lid mutant D99I was constructed by substitution of Asp99 with isoleucine after the structural alignment with Rhizomucor miehei lipase, a fungal lipase with different substrate specificity. Lid mutation could alter the substrate specificity in term of chain length specificity. The outcomes of in silico molecular docking indicates that the D99I mutant preferred the medium chain-length of substrate instead of long chain-length which is the preference for J15 lipase based on the binding energies. Gene encoding for J15 lipase was cloned into pEASY E2 vector and expressed in Escherichia coli BL21 (DE3). The mutant D99I was generated using Fast Mutagenesis Kit by changing the codon specifies the amino acid. The estimated molecular mass of mutated J15 lipase in soluble protein form was about 40.1 kDa based on the SDSPAGE analysis. The specific activity of the mutated lipase D99I was 1.66 U/mg, as compared to native J15 lipase with specific activity of 1.95 U/mg. Most of the native J15 lipase and mutated lipase were expressed as insoluble protein due to incorrect folding of protein thus rendered the characterization a difficult task. Further expression optimization or protein purification need to be done in order to collect sufficient protein for characterization studies.